Efeito da Berberina sobre testes comportamentais e atividade da Acetilcolinesterase em ratos submetidos a um modelo de demência esporádica do tipo Alzheimer - Oliveira, Juliana Sorraila de (2016)
Alzheimer's Disease (AD) is considered one of the main causes of dementia. Thus, the research for new therapeutic interventions for treatment is of utmost importance. Berberine (BRB) is an isoquinoline alkaloid that has multiple pharmacological actions including antioxidant, anti-inflammatory and neuroprotective properties. Preclinical studies have suggested their use in neurodegenerative disorders, including AD. Thus, the aim of this study was designed to investigate the effects of BRB on behavioral tests, acetylcholinesterase (AChE) activity and cell death in rat model of streptozotocin (STZ)-induced experimental dementia of Alzheimer’s type. Sixty Adult male Wistar rats were treated with BRB or saline orally once daily for 21 days and then bilaterally injected with a single intracerebroventricular-streptozotocin (ICV-STZ) (3 mg/kg, 5μL). The rats were divided into six groups (n = 10): Group I: control group; group II received BRB 50 mg/kg, group III received BRB 100 mg/kg, group IV received STZ, group V received STZ + BRB 50 mg/kg and group VI received STZ + BRB 100 mg/kg. The behavior was assessed through the Water Maze test and elevated plus maze. Behavioral parameters were assessed through Morris water maze and elevated plus maze tests. Cell death analysis and AChE activity were performed on cerebral cortex and hippocampus. The results revealed that BRB prevented memory loss, anxiogenic behavior, elevation in AChE activity and cell death induced by ICV-STZ, thereby demonstrating significant neurobehavioral and neuroprotective effects. In conclusion, our results suggest that BRB may be a potential candidate for adjuvant treatment of AD.